"Scholar physical education: is it normal?" - Rute Estanislava Tolocka; Ademir de Marco (Journal of Physical Education (Maringá), 2008)
Considering the human movement like a way of human emancipation, which is full of meaning and intention and that can be used in a criative way in the community, we propose a reflection about the medical dispense to the Physical Education class. We note the Physical Education has living a contradition: in the school the teachers can not work with the students if they have ahy king of "anormelity", out of it, they work with any king of disabled people, making possible that these people take part in sport and any other motor activities, showing how it is important to them. Among the reasons those people can not take part in the Scholar Physical Education we com find these: the goal the contents of the Scholar Physical Education, the professional preparation, the conditions whwre the classes hapen and the cultural envioronment. We suggest that it is possible to find a way that wil enable those people to work their movement in the school.